Student's interests, purposes, and attitudes towards learning French at Public Higher Educational Institutions in Malaysia - Hassan @ Hussin, Omrah; Mohamad, Ab Halim; Roslan, Amirah Syazwani (Human Resource Management Academic Research Society, 2023)
The teaching of French as a foreign language (FFL) has been introduced in the Malaysian education system since the 1980s. Following the Malaysian government's globalization policy, FFL teaching, and learning are now expanding in this nation including at the Public Higher Educational Institutions (IPTA) in Malaysia. The present study aimed to determine how interested and enthusiastic the respective IPTA students were in learning French. This quantitative study involves 329 students from twelve IPTAs: UITM, UKM, UPM, UPNM, UMK, USM, UM, USIM, UTM, UPSI, UUM, and UMT. The results of the study found that 91.8 of respondents had a strong interest in the French language. While their attitude toward the foreign language is average. To accomplish language learning objectives, interests, and attitudes must coincide. Consequently, self-learning activities such as reading newspapers, accessing the internet, and communicating in French need to be improved.